Empowering the Independent Learning-Independent Campus (MBKM) through Campus Museums - Yudhawasthi, Ciwuk Musiana (Program Studi Ilmu Perpustakaan UIN Alauddin, 2023)
As a documentary institution, museums within tertiary institutions have the potential to support and be supported by various scientific fields. This study aims to map the potential of museums in line with the Independent Learning Independent Campus (MBKM) and find out scientific collaborations that can strengthen the existence of museums in tertiary institutions in the context of MBKM. This study used a qualitative approach, using data collection techniques in the form of observation, literature review, and in-depth interviews with three supporting informants and one key informant. The study found that the higher education museum has great potential and fulfills all the requirements as an MBKM partner. Museums can be partners for internships, entrepreneurial projects, technology projects, social engineering applications, and even humanitarian projects. Museums can collaborate in informal educational activities, exchange of experts, teaching practitioners, research, and community service, all of which can involve lecturers and students from various fields of science.